Impacts of Corn Residue Grazing and Baling on Wind Erosion Potential in a Semiarid Environment. Issue 4 (21st July 2016) - Blanco-Canqui, Humberto; Tatarko, John; Stalker, Aaron L.; Shaver, Tim M.; van Donk, Simon J.
Abstract : Core Ideas: Corn residue baling increased the wind‐erodible fraction relative to no baling. Cattle grazing of corn residues had smaller effects on wind erosion than baling. As residue cover decreased, the wind‐erodible fraction increased. Soil erodibility decreased as particulate organic matter increased. Simulated soil loss showed that baling increased the wind erosion potential. Implications of corn ( Zea mays L.) residue grazing and baling on wind erosion in integrated crop–livestock systems are not well understood. This study (i) determined soil properties affecting wind erosion potential including dry aggregate‐size distribution, geometric mean diameter (GMD), geometric standard deviation of dry aggregates, and wind‐erodible fraction (WEF), (ii) correlated these properties with soil organic C (SOC) and particulate organic matter (POM), and (iii) simulated soil loss using the Single‐event Wind Erosion Evaluation Program (SWEEP) model after 7 and 8 yr of irrigated no‐till corn residue management in a semiarid region in west‐central Nebraska. Residue treatments were: control (no residue removal), light grazing (2.5 animal unit months [AUM] ha −1 ), heavy grazing (5.0 AUM ha −1 ), and baling. We simulated soil loss for a 3‐h windstorm with a wind velocity of 13 m s −1 . Soil properties differed in spring but not in fall. Baling reduced 6.3‐ to 45‐mm macroaggregates by 37% and GMD by 80% and increased WEF by 25% relative to the control. Light and heavy grazing, after 8 yr, significantly reduced 6.3‐ to 14‐mm macroaggregates 43% compared with the control and tended to reduce GMD and increase WEF, although not statistically significant. As residue cover decreased, GMD decreased and WEF increased. Residue removal did not reduce SOC and POM concentrations, but soil erodibility decreased as POM increased. Simulation showed that soil erodibility increased as residue cover decreased in spring, and baling increased the wind erosion potential. Overall, residue baling increases the wind erosion potential but residue grazing has smaller effects in this semiarid environment.